Private sector representation, contribution, and potential influence in global financing partnerships. Issue 7 (3rd October 2021) - Faul, Moira V.; Tchilingirian, Jordan Soukias
ABSTRACT: Multistakeholder financing partnerships are assumed to provide inclusive governance and mobilise private sector resources for sustainable development. Analysing the partnership space created between the board members of ten global financing partnerships allowed us to uncover two key findings. First, despite the narrative of equality in partnerships, donors continue to be privileged in this space. Second, counter to the expectation of the private sector will provide significant additional funding, their financial contribution was relatively small. High-income countries and private actors are thus privileged in decision making, and therefore wield more influence in defining which ideas of development are financed.